EFEKTIVITAS PENGAWASAN WILAYAH APRON OLEH UNIT AMC (APRON MOVEMENT CONTROL) DALAM MENJAGA KEAMANAN PADA SISI UDARA DI BANDAR UDARA RAJA HAJI FISABILILLAH TANJUNGPINANG - Arga Dinta Perdana (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This study aims to evaluate the effectiveness of the Apron Movement Control (AMC) Unit's supervision at Raja Haji Fisabilillah Airport in Tanjungpinang in maintaining security within the apron area. The AMC Unit is responsible for overseeing aircraft movements, vehicles, and personnel in the airside area, as well as ensuring the smooth operation of flights. A qualitative descriptive approach was employed, gathering data through observations, interviews, and documentation review. The findings indicate that the supervision conducted by the AMC Unit has not been optimal. Several challenges were identified, including a shortage of personnel, limited facilities, and insufficient monitoring of vehicles and personnel within the apron area. Additionally, the existing Standard Operating Procedures (SOPs) were not fully followed, particularly concerning the use of personal protective equipment by ground handling staff. To enhance the effectiveness of the supervision, recommendations include increasing the number of AMC personnel, improving supervision facilities, and separating the garbarata (jet bridge) service from apron supervision functions. This research is expected to serve as a reference for airport management in enhancing safety and security in the airside area.